Analisis Gaya Komunikasi dan Gaya Kepemimpinan Dua Presiden Legendaris Indonesia - Bambang Mudjiyanto; Galuh Sukmaranti; Hayu Lusianawati; Launa (JIKA (Jurnal Ilmu Komunikasi Andalan), 2023)
ABSTRACT Each country leader has a different communication style and leadership style. These two styles certainly do not just aim to meet the effectiveness targets of a president's communication with his people. However, these two styles must be used as indicators of the communication capacity and leadership ability of a president who is able to maintain the existence of the country and the continuity of the nation's development. This qualitative study using descriptive analysis methods based on literature and document studies tries to analyze the communication and leadership styles of President Soekarno and President Soeharto. Through searching a number of literature related to the communication styles and leadership styles of the two legendary national figures, the results of the study show: Soekarno's communication style was characterized by low-context, rhetorical, inspirational, optimistic, innovative, transformational, daring to take risks and his leadership character was characterized as charismatic, authoritative, visionary, imaginative, open, and diplomatic. Meanwhile, Soeharto's communication style is characterized by high-context, implicit, connotative, vague (even hidden), unpredictable, difficult to understand, not to the point, wordless with a leadership character that is charismatic, authoritative, dominant, delegative, transformational, visionary, transactional, situational, authoritarian, relatively closed, and anti-criticism. Keywords: Communication style, leadership style, Soekarno, Soeharto